Polar semiconductor heterojunction structure energy band diagram considerations - Lin, Shuxun; Wen, Cheng P.; Wang, Maojun; Hao, Yilong (JOURNAL OF APPLIED PHYSICS, 2016)
The unique nature of built-in electric field induced positive/negative charge pairs of polar semiconductor heterojunction structure has led to a more realistic device model for hexagonal III-nitride HEMT. In this modeling approach, the distribution of charge carriers is dictated by the electrostatic potential profile instead of Femi statistics. The proposed device model is found suitable to explain peculiar properties of GaN HEMT structures, including: (1) Discrepancy in measured conventional linear transmission line model (LTLM) sheet resistance and contactless sheet resistance of GaN HEMT with thin barrier layer. (2) Below bandgap radiation from forward biased Nickel Schottky barrier diode on GaN HEMT structure. (3) GaN HEMT barrier layer doping has negligible effect on transistor channel sheet charge density. (C) 2016 AIP Publishing LLC.